The Effectiveness of The Blood Enhancement Tablet Program In The Preven-tion of Anemia In Adolescent Girls: Systematic Literature Review - Jevin Anugrah Saputra; Rostika Flora; Nur Alam Fajar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Anemia in adolescent girls is still a fairly high public health problem in Indonesia. One of the government's efforts to prevent anemia is through the program of giving tablets added Blood (TTD) to young women. However, the compliance rate of TTD consumption is still relatively low because it is influenced by various factors, especially individual perceptions of the benefits, risks, and side effects of TTD. This study aims to analyze the perception of adolescent girls on the consumption behavior of tablets added blood based on the results of research that has been published as well as its relevance to the condition of adolescent girls in the villages and towns of Jambi province. The method used is Systematic Literature Review (SLR) with PRISMA approach. Articles are obtained from various national scientific sources relevant to the research topic. A total of 10 articles that meet the inclusion criteria were systematically analyzed based on research focus, methods, and results obtained. The results showed that the perception of adolescent girls have a significant influence on the behavior of TTD consumption. Perceptions regarding the benefits of TTD, susceptibility to anemia, the severity of anemia, and confidence in the effectiveness of TTD contribute to improving consumption compliance. On the contrary, negative perceptions related to side effects, discomfort, and lack of environmental support are the main barriers to TTD consumption. In addition to perception factors, knowledge, family support, teacher support, health workers, and peers also play a role in shaping TTD consumption behavior. Therefore, a sustainable education strategy is needed to improve the understanding and positive perception of adolescent girls towards the consumption of tablets added blood in order to reduce the rate of anemia among adolescents.